RANCANG BANGUN PROTOTYPE SMART HOME DENGAN KONSEP INTERNET OF THINGS (IOT) MENGGUNAKAN RASPBERRY PI BERBASIS WEB - Eryawan, Bagus; Jayati, Ari Endang; Heranurweni, Sri (Universitas Semarang, 2019)
High economic growth makes the demand for comfortable and safe houses increase and the application of technology that is most clearly seen is technology with automatic systems. With this technology, the use of electricity in the house can be minimized and offer convenience in controlling the house. Sometimes homeowners forget to turn off the lights when they are outside the house so they have to go back and do checks that are very inefficient both in terms of time and financially such as the cost of gasoline to return to the house. Based on this, the Smart Home Prototype was created with the concept of the Internet of Things (IoT) using Raspberry Pi Web-Based, which is a system that can remotely control electronic home appliances using Raspberry Pi as a base system, which is connected to Web Applications through the internet network. The electronic equipment used in this study is in the form of 5 lamps, 1 stepper motor to control the garage, 1 servo motor to control the door lock, and 1 brushless motor that functions as a fan. Blocking and overall test results on Bedroom Lights, Living Room Lights, Kitchen Lights, Bathroom Lights, Porch Lights, Garages, Door Locks, and Fans, all work well. The testing of the distance between cities against the Prototype Smart Home was successfully carried out, where the Prototype Smart Home in the City of Demak was successfully controlled by the User who at the time of testing was in the City of Semarang, Kudus, Japan, Surabaya, and Jakarta.